Dampak Durasi dan Kualitas Screen Time terhadap Kesejahteraan Sosial-Emosional Anak Usia Dini - Winarni Putria Chandra; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This reaserch aims to analyze the impact of screen time duration and content quality on the social-emotional well-being of early childhood. The study employed a qualitative description methode with a literature review appoarch, synthesizing date from various scientific articles and relevan field reports. Findings indicate that excessive screen time duration ( more than one hour per day) correlates significantly with desreased social interaction skills and emotional regulation difficulties in children. Conversely, high-quality educational content, when accompanied by parental mediation, can support cognitive development without harming emotional stability. The reaserch recommends that parents and educators estabils strict digital boundaries and prioritize high-quality interactive content to maintain children’s emotional health in the diggital era. Standard nomencalture is used throughout, and no literatur is cited within this summary